THE INFLUENCE OF SOFT SKILLS AND E-COMMERCE DEVELOPMENT ACTIVITIES ON INCREASING INCOME DURING THE COVID-19 PANDEMIC IN THE WOMEN'S BUSINESS GROUP IN JATIREJO VILLAGE - Evi Fitrotun Najiah; Henny Mahmudah; Niken Agustin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The Jatirejo village government during the Covd-19 pandemic sees the need for soft skills and e-commerce development activities that are intended primarily for residents/communities. This is considered very useful in increasing the income of the people in Jatirejo village during the Covid-19 pandemic. In this activity, the village government held training for people who have businesses and people who are unemployed as a result of the impact of the pandemic in hamlets such as Topeng Hamlet, Kemendung Hamlet, Karangpilang Hamlet and Tambakjurit Hamlet.The purpose of this study was to determine whether soft skills and E-Commerce, either partially or simultaneously, had an effect on increasing income during the Covid 19 pandemic in the women's business group in Jatirejo Village. In this research, quantitative descriptive method is used by looking at the impact of the activities that have been carried out on increasing income. This activity was started first with observations and interviews, then continued with multiple linear regression testing, Partial Hypothesis (t-test) and Simultaneous Hypothesis (F-Test) using the SPSS tool.The results of this study obtained Multiple Linear Regression test Y = 8.702 + 0.241X1 +0.732X2 , Partial Hypothesis Test t obtained t value (soft skill) 2.105; the value of t arithmetic (E-Commerce) 4.271 is greater than the value of t table 2.032 with = 0.05. significance value 0.000 0.05, the results of the Simultaneous Hypothesis test obtained Fcount 33.351 F table 3.28 with = 0.05. significance value 0.000 0.05. Then Ho is rejected and H1 is accepted.From the results of this study, it can be concluded that soft skills and E-Commerce, both partially and simultaneously, have an effect on increasing income during the Covid 19 pandemic in the Jatirejo Village women's business group and the most dominant influencing variable is E-Commerce.